Construction Cost and Carbon Emission Assessment of a Highway Construction—A Case towards Sustainable Transportation - Wenkai Luo (Sustainability, 2021)
Due to its dynamic nature in construction, benchmarking environmental emissions of road construction projects can be a daunting task. Often stakeholders will have to prioritize the economic and environmental indicators based on the project objectives. The study presents a methodological framework to compare economic and environmental impacts to benchmark sustainable transport construction projects. Through findings, the study aims to inform focus areas and key stages of infrastructure projects to benchmark sustainable performance. Process-based emission and cost estimation models are presented with an AHP based weighting factor that enables prioritization of emissions and costs based on project scopes and objectives. Using a case study, results are represented to validate the framework and methodology. Concrete and steel are identified as the main materials that contribute to total carbon emissions, while soil and gravel are responsible for the highest costs. Electricity consumption is discovered as the major fuel type contributing to carbon emissions. Concrete and dump trucks are discovered as the top two sources of emissions and costs, respectively. Scenario analyses revealed that the choice of equipment significantly affects the project’s emissions and costs. The application of sustainable materials can significantly reduce emissions and cost. The use of the case study approach results in a lack of generalizability. However, the same methodology and process can be adopted for the sustainable benchmarking of different projects. Researchers are encouraged to investigate processes to automate sustainable benchmarking of transport infrastructure construction projects. The study is one of the first attempts to compare cost and environmental impacts using a systematic methodology of transportation infrastructure construction projects.